In-situ cured organic-inorganic composite solid electrolyte, solid-state battery and preparation method of solid-state battery

By forming an inorganic oxide layer on the surface of the positive electrode material of the lithium-ion battery and forming an organic solid electrolyte, the problem of insufficient electrochemical performance and thermal runaway of the positive electrode material of the lithium-ion battery at high voltage is solved, and higher cycle stability and safety are achieved sex.

CN119153762AInactive Publication Date: 2024-12-17SHANDONG GOLDEN RACE ENERGY GRP CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411062307.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrochemical performance of the existing lithium-ion batteries is insufficient at high voltage, and there is a risk of thermal runaway. It is difficult to completely avoid contact between the positive electrode material and the electrolyte components, resulting in insufficient safety.

Method used

The surface of the positive electrode material is cured in situ to form an inorganic oxide layer, and an organic solid electrolyte is formed by in situ curing to form an organic inorganic composite solid electrolyte, improving electrochemical performance and safety.

Benefits of technology

Effectively improve the electrochemical performance of the positive electrode material at high voltage, reduce the risk of positive electrode overheating, enhance the cycle stability and safety performance of the battery, form a complete lithium-ion channel, reduce side reactions, and improve the safety performance of the battery .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of an in-situ cured organic-inorganic composite solid electrolyte, which comprises the following steps of: in the process of preparing a positive pole piece, performing in-situ curing on the surface of an active positive pole material to form an inorganic oxide layer; and after the dry cell is processed, the organic solid electrolyte is formed through in-situ curing. The invention discloses the in-situ cured organic-inorganic composite solid electrolyte which is prepared by the preparation method. The invention discloses a preparation method of an in-situ cured organic-inorganic composite solid-state battery, which comprises the following steps: processing into a dry cell, and then forming an organic solid-state electrolyte through in-situ curing; and forming the solid-state battery of the organic-inorganic composite solid-state electrolyte after formation and capacity grading. The invention discloses an in-situ cured organic-inorganic composite solid-state battery which is prepared by the preparation method. The electrochemical performance of the positive electrode material under high voltage is improved, overheat of the positive electrode is relieved, and the method is very suitable for popularization and application in the industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of new materials and new energy technologies, and in particular, to solid electrolytes and solid batteries, and methods for preparing the electrolytes and solid batteries. Background Art

[0002] At present, lithium-ion batteries have the characteristics of high energy density and long life, and are widely used in portable electronic devices, electric vehicles, energy storage systems and other fields. With the popularization of lithium-ion batteries, corresponding safety accidents occur frequently. The main reason is that the electrolyte of traditional lithium-ion batteries uses flammable organic solvents. Solid electrolytes can improve the safety issues of lithium-ion batteries. Solid electrolytes can be mainly divided into three categories according to their types: polymer solid electrolytes, oxide solid electrolytes, and sulfide solid electrolytes. A single type of solid electrolyte is difficult to meet the requirements, and the existing solid electrolytes are basically composite solid electrolytes.

[0003] In-situ polymerization is a simple method for preparing polymer electrolytes that is compatible with existing commercial battery production. It can obtain thin and uniform polymer electrolytes. Through in-situ curing technology, the polymer turns the flowing electrolyte into a solid state, reducing the safety risk of the battery. For example, invention CN114665151A uses an in-situ polymerization curing method to prepare an in-situ cured electrolyte, which improves the interface compatibility of solid-state batteries, reduces the manufacturing cost of solid-state batteries, and improves the performance of solid-state batteries. The monomers of the polymer electrolyte include cyclopentene structure monomers and active hydrogen structure monomers. The polymer electrolyte has excellent thermal stability and can generate a chemically integrated interface with the electrode during the battery curing stage to improve the interface performance. Invention CN111786017A provides a high-adhesive solid electrolyte prepared by in-situ curing, a preparation method and a secondary lithium battery composed thereof. The high-adhesive solid electrolyte raw materials are mainly composed of terminal hydroxyl oligomers, terminal isocyanate compounds, and lithium salts. Through in-situ curing, the positive and negative electrodes and the electrolyte are closely fitted, and the interface impedance between the electrolyte and the positive and negative electrodes is reduced, thereby achieving the effect of improving the battery rate performance and cycle performance. The preparation process of solid-state lithium batteries has been greatly simplified, the interface contact has been optimized, the danger of misalignment has been prevented, and the safety of the battery has been improved. However, the use of in-situ polymerized polymer solid electrolyte batteries alone cannot completely change the safety of the battery, cannot completely avoid the contact between the positive electrode material and the electrolyte components, and still has the risk of thermal runaway.

[0004] Therefore, how to improve the electrochemical performance of positive electrode materials under high voltage and alleviate positive electrode overheating is a technical problem that the industry urgently needs to solve. Summary of the invention

[0005] A main purpose of the present invention is to overcome at least one defect of the above-mentioned prior art and to provide an in-situ solidified organic-inorganic composite solid electrolyte and solid-state battery and a preparation method thereof, which can improve the electrochemical performance of the positive electrode material under high voltage and alleviate the overheating of the positive electrode.

[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0007] According to one aspect of the present invention, there is provided a method for preparing an in-situ cured organic-inorganic composite solid electrolyte, comprising the following steps: in the process of preparing the positive electrode plate, in-situ curing is performed on the surface of the active positive electrode material to form an inorganic oxide layer; after being processed into a dry battery cell, an organic solid electrolyte is formed by in-situ curing.

[0008] According to one embodiment of the present invention, the following steps are included: mixing the positive electrode material, the coating agent, the conductive agent, and the binder, adding the solvent N-methylpyrrolidone to form a slurry, coating the slurry on the positive electrode collector, baking, rolling and die-cutting, and placing the slurry in an oven for vacuum drying to form a solid-state battery positive electrode sheet.

[0009] According to one embodiment of the present invention, the positive electrode material is at least one of lithium cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese aluminum oxide, and lithium iron phosphate; the coating agent is at least one of aluminum isopropoxide, titanium isopropoxide, titanium tetrachloride, tetra-n-butyl titanate, and tetraethoxysilane; the mass ratio of the positive electrode material, coating agent, conductive agent, and binder is (80-97): (1-10): (1-5): (1-5); the temperature of the vacuum drying in the oven is 100-150°C, and the baking time is 12-48h.

[0010] According to a second aspect of the present invention, there is provided an in-situ solidified organic-inorganic composite solid electrolyte, which is prepared by the above-mentioned preparation method.

[0011] According to the third aspect of the present invention, there is provided a method for preparing an in-situ cured organic-inorganic composite solid-state battery, comprising the steps described above, and further comprising the following steps: after being processed into a dry battery cell, an organic solid electrolyte is formed by in-situ curing; after being divided into components, a solid-state battery of an organic-inorganic composite solid electrolyte is formed.

[0012] According to one embodiment of the present invention, the following steps are included:

[0013] The positive electrode material, coating agent, conductive agent and binder are mixed, and the solvent N-methylpyrrolidone is added to form a slurry, which is applied to the positive electrode collector, and after baking, rolling and die-cutting, it is placed in an oven for vacuum drying to form a positive electrode sheet of a solid-state battery;

[0014] The positive electrode sheet, separator and negative electrode sheet of the solid-state battery are assembled into a dry battery cell by stacking, and after baking, the electrolyte prepolymer is injected. After room temperature infiltration and pressurized high-temperature polymerization, the cells are divided into volumes to obtain an organic-inorganic composite solid-state battery.

[0015] According to one embodiment of the present invention, the diaphragm is one of a ceramic coated diaphragm, a rubber coated diaphragm, and a solid electrolyte coated diaphragm; the negative electrode sheet is one of a graphite negative electrode sheet, a silicon carbon negative electrode sheet, a silicon oxide graphite negative electrode sheet, or a lithium metal negative electrode sheet; the infiltration time is 12-48h; the pressure in the pressurized high temperature polymerization is 100-1000kgf, the temperature is 50-80°C, and the polymerization time is 3-24h.

[0016] According to one embodiment of the present invention, the electrolyte prepolymer is composed of three parts: an organic electrolyte, a polymer monomer, and an initiator;

[0017] The mass percentages of the organic electrolyte, the polymer monomer and the initiator in the electrolyte prepolymer are: (80-99.7): (0.3-20): (0.005-1).

[0018] According to one embodiment of the present invention, the polymer monomer is selected from at least one of 1,3-dioxolane, methyl methacrylate, ethyl methacrylate, triethylene glycol methacrylate, di(trimethylolpropane) tetraacrylate, propylene glycol monomethyl ether acetate, vinylene carbonate, cyanopolyvinyl alcohol, ethylene acrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, 2-methacrylate-2-oxirane ethyl ester, polyethylene glycol diglycidyl ether, polyethylene glycol dimethyl ether, N,N-dimethylacrylamide, N,N-methylenebisacrylamide, etc.;

[0019] The initiator comprises at least one of benzoyl peroxide, azobisisobutyronitrile, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, azobisisoheptylnitrile, dimethyl azobisisobutyrate, tri-n-butyl phosphine, triethyl phosphine, triphenyl phosphine, tributyltin oxide, stannous octoate, tetrabutyl zirconate, N-methylethylenediamine, dimethylformamide, aluminum trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, tin trifluoromethanesulfonate and lithium bis(fluorosulfonyl)imide, dialkyltin oxide and trialkyltin alkoxide.

[0020] According to a fourth aspect of the present invention, there is provided an in-situ cured organic-inorganic composite solid-state battery, which is prepared by the above-mentioned preparation method.

[0021] It can be seen from the above technical scheme that the advantages and positive effects of the in-situ solidified organic-inorganic composite solid electrolyte and solid-state battery and the preparation method thereof of the present invention are:

[0022] In the present invention, an inorganic oxide layer is formed by in-situ solidification on the surface of the active positive electrode material, and then an organic solid electrolyte is formed, so as to improve the electrochemical performance of the positive electrode material under high voltage and alleviate the overheating of the positive electrode, which is very suitable for promotion and use in the industry. DETAILED DESCRIPTION

[0023] Reference will now be made to more fully describing example embodiments. However, example embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present invention will be comprehensive and complete and fully convey the concept of the example embodiments to those skilled in the art.

[0024] In the following description of different examples of the present invention, different exemplary structures, systems and steps that can implement multiple aspects of the present invention are shown by way of example. It should be understood that other specific schemes of components, structures, exemplary devices, systems and steps can be used, and structural and functional modifications can be made without departing from the scope of the present invention. Moreover, although the terms "top", "bottom", "front", "rear", "side" and the like may be used in this specification to describe different exemplary features and elements of the present invention, these terms are used herein only for convenience, such as according to the direction of the examples described. Nothing in this specification should be construed as requiring a specific three-dimensional orientation of the structure to fall within the scope of the present invention.

[0025] The present invention forms an organic-inorganic composite solid electrolyte layer by means of two in-situ curing processes, thus providing a double insurance for battery safety. Specifically, first, during the preparation of the positive electrode sheet, an inorganic oxide layer is formed by in-situ curing on the surface of the active positive electrode material. After being processed into a dry battery cell, an organic solid electrolyte is formed by in-situ curing, and after the components are divided into different capacities, a solid-state battery of an organic-inorganic composite solid electrolyte is formed. The two in-situ curing methods provided by the present invention can effectively improve the solid-solid interface contact, improve the ionic conductivity of the battery, and improve the stability of the positive electrode material. The manufactured solid-state battery exhibits excellent cycle stability and safety.

[0026] One of the purposes of the present invention is to provide an in-situ solidified organic-inorganic composite solid electrolyte.

[0027] A second object of the present invention is to provide a solid battery with an in-situ solidified organic-inorganic composite solid electrolyte.

[0028] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0029] In a first aspect, the present invention provides an in-situ solidified organic-inorganic composite solid electrolyte, comprising the following steps:

[0030] (1) Preparation of in-situ solidified inorganic solid electrolyte: The preparation of inorganic solid electrolyte is carried out along with the preparation of the positive electrode sheet of the solid-state battery. Specifically, the positive electrode material, coating agent, conductive agent, and binder are mixed, and the solvent N-methylpyrrolidone (NMP) is added to form a slurry, which is then coated on the positive electrode collector. After baking, roller pressing and die cutting, it is placed in an oven for vacuum drying to form a positive electrode sheet of the solid-state battery. After the coating agent is hydrolyzed, a layer of inorganic solid electrolyte is coated on the surface of the positive electrode material.

[0031] (2) Preparation of in-situ solidified organic solid electrolyte: The positive electrode of the solid-state battery is made into a dry battery cell, and the electrolyte prepolymer is injected. After room temperature infiltration and pressurized high temperature polymerization, an organic polymer solid electrolyte is formed.

[0032] (3) Composite organic-inorganic solid electrolyte: The prepared battery cell is chemically divided into components to obtain an organic-inorganic composite solid electrolyte.

[0033] The following is a detailed description:

[0034] Step (1):

[0035] The positive electrode material is at least one of lithium cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese aluminum oxide, and lithium iron phosphate;

[0036] The coating agent is at least one of aluminum isopropoxide, titanium isopropoxide, titanium tetrachloride, tetra-n-butyl titanate, tetrabutyl zirconate and tetraethoxysilane;

[0037] The conductive agent is a common conductive carbon material in the art, such as at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon fibers, graphene, etc.;

[0038] The binder is at least one of polyvinylidene fluoride and polytetrafluoroethylene commonly used in the art;

[0039] The mass ratio of the positive electrode material, coating agent, conductive agent and binder is (80-95): (1-10): (1-5): (1-5);

[0040] The viscosity of the slurry is 1000-9000 mPa·s;

[0041] The temperature of the oven vacuum drying treatment is 100-150° C., and the baking time is 12-48 hours.

[0042] Step (2):

[0043] The electrolyte prepolymer is composed of three parts: organic electrolyte, polymer monomer and initiator;

[0044] The mass percentages of the organic electrolyte, the polymer monomer and the initiator in the electrolyte prepolymer are: (80-99.7): (0.3-20): (0.005-1).

[0045] The polymer monomer is selected from at least one of 1,3-dioxolane, methyl methacrylate, ethyl methacrylate, triethylene glycol methacrylate, di(trimethylolpropane) tetraacrylate, propylene glycol monomethyl ether acetate, vinylene carbonate, cyanopolyvinyl alcohol, ethylene acrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, 2-methacrylate-2-oxirane ethyl ester, polyethylene glycol diglycidyl ether, polyethylene glycol dimethyl ether, N,N-dimethylacrylamide, N,N-methylenebisacrylamide, etc.;

[0046] The initiator comprises at least one of benzoyl peroxide, azobisisobutyronitrile, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, azobisisoheptylnitrile, dimethyl azobisisobutyrate, tri-n-butyl phosphine, triethyl phosphine, triphenyl phosphine, tributyltin oxide, stannous octoate, tetrabutyl zirconate, N-methylethylenediamine, dimethylformamide, aluminum trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, tin trifluoromethanesulfonate and lithium bis(fluorosulfonyl)imide, dialkyltin oxide and trialkyltin alkoxide.

[0047] The injection amount of the electrolyte prepolymer is 1-4 g / Ah.

[0048] The infiltration time is 12-48h;

[0049] The pressure in the pressurized high temperature polymerization is 100-1000 kgf, the temperature is 50-80° C., and the polymerization time is 3-24 hours.

[0050] In a second aspect, the present invention provides a solid-state battery of an in-situ solidified organic-inorganic composite solid electrolyte, specifically:

[0051] The positive electrode sheet, separator and negative electrode sheet of the solid-state battery are assembled into a dry battery cell by stacking, and after baking, the electrolyte prepolymer is injected. After room temperature infiltration and pressurized high-temperature polymerization, the cells are divided into volumes to obtain an organic-inorganic composite solid-state battery.

[0052] In the process of preparing the organic-inorganic composite solid electrolyte, an organic-inorganic composite solid battery is obtained at the same time, so the implementation of this scheme includes all the requirements of the first aspect, in addition, it should also include:

[0053] The single-sided surface density of the solid-state battery positive electrode sheet is 10 to 30 mg / cm 2 , preferably 15-20 mg / cm 2 ;

[0054] The thickness of the solid-state battery positive electrode plate is 80 μm to 200 μm, preferably 100 μm to 130 μm.

[0055] The diaphragm is one of a polyethylene diaphragm, a polypropylene diaphragm, an aramid diaphragm, a polyimide diaphragm, a ceramic-coated diaphragm, a rubber-coated diaphragm, and a solid electrolyte-coated diaphragm;

[0056] The negative electrode sheet is one of the common graphite negative electrode sheets, silicon-carbon negative electrode sheets, silicon-oxygen-graphite negative electrode sheets or lithium metal negative electrode sheets in the art;

[0057] Beneficial effects:

[0058] 1. The in-situ curing method adopted by the present invention coats a layer of oxide material on the surface of the positive electrode material, which can reduce or avoid direct contact between the active substance and the electrolyte, thereby inhibiting the occurrence of side reactions between the positive electrode material and the electrolyte, inhibiting the structural damage of the positive electrode material during the charge and discharge process, and improving the structural stability of the material surface. It can significantly improve the electrochemical performance of the positive electrode material under high voltage and increase the cycle life of the battery.

[0059] 2. The oxide on the surface of the positive electrode material in the present invention effectively blocks the contact between the active particles of the positive electrode material, thereby improving the thermal stability of the material; secondly, the oxide of the present invention can absorb part of the heat generated by the positive electrode, thereby alleviating overheating of the positive electrode.

[0060] 3. The polymer obtained by in-situ polymerization in the present invention can effectively improve the contact between the oxide solid electrolyte and the material in the positive electrode sheet, reduce the impedance of the positive electrode sheet, and improve the electrochemical performance of the positive electrode sheet.

[0061] 4. The combination of oxide solid electrolyte and polymer solid electrolyte in the present invention enables the positive electrode sheet of the present invention to have excellent electrochemical performance on the basis of excellent safety performance. The solid-state battery provided by the present invention forms a complete lithium ion conductive channel inside the positive and negative electrode sheets, reduces the side reaction between the active material and the electrode, and greatly improves the safety performance of the battery cell.

[0062] Example 1

[0063] Positive electrode: Ni80(Li(Ni 0.8 Co 0.1 Mn 0.1 O 2 )) The ternary material, conductive carbon black, carbon nanotubes, aluminum isopropoxide and polyvinylidene fluoride are mixed in a mass ratio of 95:1.2:0.8:1.5:1.5, and the solvent NMP is added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry is controlled at 3000mPa·s. The slurry is coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating is controlled to be 15mg / cm 2After the coated electrode is rolled, the thickness of the electrode is 110 μm. After die-cutting, it is placed in a 120°C oven for vacuum drying for 12 hours to obtain a solid-state battery positive electrode.

[0064] Negative electrode sheet: artificial graphite, silicon oxide, conductive carbon black, single-walled carbon nanotubes, sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid binder are mixed in a mass ratio of 86:10:0.6:0.3:0.6:0.5:2, deionized water is added for homogenization, and the mixture is coated on the surface of copper foil. After drying, rolling and die-cutting, the negative electrode sheet is obtained.

[0065] Solid-state battery dry cell: After the solid-state battery positive electrode sheet, negative electrode sheet, and solid electrolyte LATP coated diaphragm are stacked, welded, and top and side sealed, a solid-state battery soft-pack dry cell is obtained.

[0066] Electrolyte prepolymer: At room temperature, 3 wt% polyethylene glycol diacrylate and 0.01 wt% azobisisobutyronitrile initiator were added to 97.99 wt% organic electrolyte (1 M LiPF 6 / EC+EMC+DMC), stirred for 30 minutes, and allowed to stand at room temperature for 12 hours to obtain an electrolyte prepolymer. The electrolyte prepolymer can be stored in a refrigerator with a shelf life of 7 days.

[0067] Solid-state battery: The solid-state battery dry cell is vacuum dried at 100°C for 24 hours, 20g of electrolyte prepolymer is injected into the dry cell, and after being soaked at room temperature of 25°C for 48 hours, the cell is subjected to high-temperature treatment at 80°C and 500kgf pressure for 8 hours. After formation, aging, degassing, secondary sealing, and capacity separation, a solid-state battery of about 10Ah is obtained.

[0068] The prepared solid-state battery was tested for capacity, cycle performance, heating, acupuncture and other safety performance tests. Five cells were used for heating and acupuncture safety tests to see the pass rate. The test results are shown in Table 1.

[0069] Test method:

[0070] Capacity: The capacity is obtained by performing a 1C / 1C charge and discharge test on the battery cell at 25±2℃.

[0071] Capacity retention rate: Under the condition of 25±2℃, the battery cell is charged and discharged at 1C / 1C and the capacity retention rate of 500 cycles;

[0072] Heating: Charge the test cell at 1C to 100% SOC, then heat it from room temperature to 150°C at a heating rate of 5°C / min, keep it warm for 30 minutes, then continue to heat it at 5°C / min, and keep it warm for 30 minutes every 5°C rise. If there is no explosion, fire, or rupture during the test, the battery passes;

[0073] Acupuncture: The battery is charged at 1C constant current and constant voltage, with a cut-off current of 0.05C; The high temperature resistant steel needle penetrates the battery plate at a speed of 25±5mm / s from a direction perpendicular to the battery plate. The penetration position should be close to the geometric center of the pierced surface. The steel needle stays in the battery. Observe for 30 minutes, monitor the change of the surface temperature of the battery cell during the process, and record whether the battery cell catches fire or explodes. If there is no explosion, fire or rupture during the test, the battery passes;

[0074] The test methods of the following embodiments and comparative examples are all implemented in the above-mentioned manner.

[0075] Example 2

[0076] Positive electrode: Ni88(Li(Ni 0.88 Co 0.09 Mn 0.03 O 2 )) The ternary material, conductive carbon black, carbon nanotubes, tetrabutyl zirconate, titanium isopropoxide and polyvinylidene fluoride are mixed in a mass ratio of 94:0.5:1:1.5:1:2, and the solvent NMP is added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry is controlled at 5000mPa·s. The slurry is coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating is controlled to be 13mg / cm 2 After the coated electrode is rolled, the thickness of the electrode is 100 μm. After die-cutting, it is placed in a 130°C oven for vacuum drying for 8 hours to obtain a solid-state battery positive electrode.

[0077] The preparation of the negative electrode is the same as in Example 1.

[0078] Solid-state battery dry cell: After the solid-state battery positive electrode sheet, negative electrode sheet, and ceramic-coated diaphragm are stacked, welded, and top and side sealed, a solid-state battery soft-package dry cell is obtained.

[0079] Electrolyte prepolymer: At room temperature, 5 wt% methyl methacrylate and 0.02 wt% azobisisobutyronitrile initiator were added to 94.98 wt% organic electrolyte (1M LiPF 6 / EC+EMC), stirred for 30 minutes, and allowed to stand at room temperature for 12 hours to obtain an electrolyte prepolymer. The electrolyte prepolymer can be stored in a refrigerator with a shelf life of 7 days.

[0080] Solid-state battery: The solid-state battery dry cell is vacuum dried at 100°C for 24 hours, 40g of electrolyte prepolymer is injected into the dry cell, and after being soaked at room temperature of 25°C for 48 hours, the cell is subjected to high-temperature treatment at 70°C and 900kgf pressure for 12 hours. After formation, aging, degassing, secondary sealing, and capacity separation, a solid-state battery of about 10Ah is obtained.

[0081] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0082] Example 3

[0083] Positive electrode: Ni83(Li(Ni 0.83 Co 0.12 Mn 0.05 O 2 )) The ternary material, conductive carbon black, tetraethoxysilane and polyvinylidene fluoride are mixed in a mass ratio of 92:3:3:2, and the solvent NMP is added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry is controlled at 4000mPa·s. The slurry is coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating is controlled to be 20mg / cm 2 After the coated electrode is rolled, the thickness of the electrode is 130 μm. After die-cutting, it is placed in a 110°C oven for vacuum drying for 18 hours to obtain a solid-state battery positive electrode.

[0084] Negative electrode sheet: artificial graphite, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 96.5:0.5:1:2, deionized water is added for homogenization, and the mixture is coated on the surface of copper foil. The negative electrode sheet is obtained after drying, rolling and die-cutting.

[0085] Solid-state battery dry cell: After the solid-state battery positive electrode sheet, negative electrode sheet and glue-coated diaphragm are stacked, welded and top and side sealed, a solid-state battery soft-pack dry cell is obtained.

[0086] Electrolyte prepolymer: At room temperature, 1 wt% pentaerythritol tetraacrylate and 0.05 wt% azobisisobutyronitrile initiator were added to 98.95 wt% organic electrolyte (1M LiPF 6 / EC+DEC), stirred for 30 minutes, and allowed to stand at room temperature for 12 hours to obtain an electrolyte prepolymer. The electrolyte prepolymer can be stored in a refrigerator with a shelf life of 7 days.

[0087] Solid-state battery: The solid-state battery dry cell is vacuum dried at 100°C for 24 hours, 30g of electrolyte prepolymer is injected into the dry cell, and after being soaked at room temperature of 25°C for 36 hours, the cell is subjected to high-temperature treatment at 60°C and 800kgf pressure for 10 hours. After formation, aging, degassing, secondary sealing, and capacity separation, a solid-state battery of about 10Ah is obtained.

[0088] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0089] Example 4

[0090] Positive electrode: LiCoO 2 The material, single-walled carbon nanotubes, titanium isopropoxide and polyvinylidene fluoride were mixed in a mass ratio of 92:0.5:5:2.5, and the solvent NMP was added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry was controlled at 7000mPa·s. The slurry was coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating was controlled to be 17mg / cm 2 After the coated electrode is rolled, the thickness of the electrode is 120 μm. After die-cutting, it is placed in a 120°C oven for vacuum drying for 12 hours to obtain a solid-state battery positive electrode.

[0091] The negative electrode plate is the same as that in Example 3.

[0092] Solid-state battery dry cell: After the solid-state battery positive electrode sheet, negative electrode sheet and polyimide separator are stacked, welded and top and side sealed, a solid-state battery soft-package dry cell is obtained.

[0093] Electrolyte prepolymer: At room temperature, 10 wt% polyethylene glycol diacrylate and 1 wt% azobisisobutyronitrile initiator were added to 89 wt% organic electrolyte (1M LiPF 6 / EC+EMC+DMC), stirred for 30 minutes, and allowed to stand at room temperature for 12 hours to obtain an electrolyte prepolymer. The electrolyte prepolymer can be stored in a refrigerator with a shelf life of 7 days.

[0094] Solid-state battery: The solid-state battery dry cell is vacuum dried at 110°C for 24 hours, the electrolyte prepolymer is injected into the dry cell, and after being soaked at room temperature of 25°C for 36 hours, the cell is subjected to high-temperature treatment at 70°C and 900kgf pressure for 18 hours. After formation, aging, degassing, secondary sealing, and capacity separation, a solid-state battery of about 10Ah is obtained.

[0095] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0096] Example 5

[0097] Positive electrode: NCA (LiNi 0.8 Co 0.15 Al 0.05 O 2 ) material, conductive carbon black, carbon nanotubes, tetrabutyl titanate and polyvinylidene fluoride were mixed in a mass ratio of 92.5:0.5:1.2:3.3:2.5, and the solvent NMP was added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry was controlled at 8000mPa·s. The slurry was coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating was controlled to be 16mg / cm 2After the coated electrode is rolled, the thickness of the electrode is 110 μm. After die-cutting, it is placed in a 110°C oven for vacuum drying for 18 hours to obtain a solid-state battery positive electrode.

[0098] Negative electrode sheet: artificial graphite, fumed silicon carbon, conductive carbon black, single-walled carbon nanotubes, sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid binder are mixed in a mass ratio of 84:12:0.5:0.2:0.3:0.5:2.5, deionized water is added for homogenization, and the mixture is coated on the surface of copper foil. After drying, rolling and die-cutting, the negative electrode sheet is obtained.

[0099] Solid-state battery dry cell: After the solid-state battery positive electrode sheet, negative electrode sheet and aramid diaphragm are stacked, welded and top and side sealed, a solid-state battery soft-package dry cell is obtained.

[0100] Electrolyte prepolymer: At room temperature, 8 wt% vinylene carbonate and 1 wt% benzoyl peroxide initiator were added to 91 wt% organic electrolyte (1M LiPF 6 / EC+EMC), stirred for 30 minutes, and allowed to stand at room temperature for 12 hours to obtain an electrolyte prepolymer. The electrolyte prepolymer can be stored in a refrigerator with a shelf life of 7 days.

[0101] Solid-state battery: The solid-state battery dry cell is vacuum dried at 100°C for 24 hours, 25g of electrolyte prepolymer is injected into the dry cell, and after being soaked at room temperature of 25°C for 48 hours, the cell is subjected to high-temperature treatment at 50°C and 600kgf pressure for 18 hours. After formation, aging, degassing, secondary sealing, and capacity separation, a solid-state battery of about 10Ah is obtained.

[0102] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0103] Example 6

[0104] Positive electrode: Ni92(Li(Ni 0.92 Co 0.05 Mn 0.03 O 2 )) material, conductive carbon black, graphene, tetrabutyl zirconate and polyvinylidene fluoride are mixed in a mass ratio of 92:2:0.1:4:1.9, and a solvent NMP is added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry is controlled at 5000mPa·s. The slurry is coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating is controlled to be 15mg / cm 2 After the coated electrode is rolled, the thickness of the electrode is 110 μm. After die-cutting, it is placed in a 120°C oven for vacuum drying for 12 hours to obtain a solid-state battery positive electrode.

[0105] The negative electrode uses metallic lithium foil.

[0106] Solid-state battery dry cell: After the solid-state battery positive electrode sheet, negative electrode sheet, and solid electrolyte coated diaphragm are stacked, welded, and top and side sealed, a solid-state battery soft-pack dry cell is obtained.

[0107] Electrolyte prepolymer: At room temperature, 5 wt% cyanopolyvinyl alcohol and 1 wt% tri-n-butylphosphine initiator were added to 94 wt% organic electrolyte (1M LiPF 6 / EC+EMC+DMC), stirred for 30 minutes, and allowed to stand at room temperature for 12 hours to obtain an electrolyte prepolymer. The electrolyte prepolymer can be stored in a refrigerator with a shelf life of 7 days.

[0108] Solid-state battery: The solid-state battery dry cell is vacuum dried at 100°C for 24 hours, 20g of electrolyte prepolymer is injected into the dry cell, and after being soaked at room temperature of 25°C for 36 hours, the cell is subjected to high-temperature treatment at 70°C and 500kgf pressure for 10 hours. After formation, aging, degassing, secondary sealing, and capacity separation, a solid-state battery of about 10A is obtained.

[0109] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0110] Comparative Example 1

[0111] Positive electrode: Ni83(Li(Ni 0.83 Co 0.12 Mn 0.05 O 2 )) The ternary material, conductive carbon black, carbon nanotubes and polyvinylidene fluoride are mixed in a mass ratio of 96.5:1.5:0.5:1.5, and the solvent NMP is added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry is controlled at 5000mPa·s. The slurry is coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating is controlled to be 16mg / cm 2 After the coated electrode is rolled, the thickness of the electrode is 110 μm. After die-cutting, it is placed in a 120°C oven for vacuum drying for 18 hours to obtain a solid-state battery positive electrode.

[0112] The negative electrode is the same as in Example 3.

[0113] Battery: After stacking the positive electrode, negative electrode and ceramic-coated diaphragm of the solid battery, welding and top-side sealing are performed, a soft-pack dry cell is obtained. The dry cell is vacuum dried at 100°C for 24 hours, and 30g of electrolyte (1M LiPF 6 / EC+EMC) is injected into the dry battery cell, and after being immersed at room temperature of 25°C for 48 hours, the battery cell is subjected to high-temperature treatment at a temperature of 80°C and a pressure of 500kgf for 8 hours. After formation, aging, degassing, secondary sealing, and capacity division, a battery of about 10Ah is obtained.

[0114] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0115] Comparative Example 2

[0116] Positive electrode: Ni80(Li(Ni 0.8 Co 0.1 Mn 0.1 O 2 )) The ternary material, conductive carbon black, carbon nanotubes, tetrabutyl titanate and polyvinylidene fluoride are mixed in a mass ratio of 94.5:1.0:0.8:2.2:1.5, and the solvent NMP is added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry is controlled at 4000mPa·s. The slurry is coated on the positive electrode current collector aluminum foil by a coating machine, and the single-sided surface density of the coating is controlled to be 20mg / cm 2 After the coated electrode is rolled, the thickness of the electrode is 140 μm. After die-cutting, it is placed in a 130°C oven for vacuum drying for 18 hours to obtain a solid-state battery positive electrode.

[0117] The negative electrode is the same as in Example 5

[0118] Battery: After stacking the positive electrode, negative electrode and ceramic-coated diaphragm of the solid battery, welding and top-side sealing are performed, a soft-pack dry cell is obtained. The dry cell is vacuum dried at 120°C for 18 hours, and 35g of electrolyte (1M LiPF 6 / EC+EMC) was injected into the dry battery cell, and after soaking for 48 hours at room temperature of 25°C, and then subjected to formation, aging, degassing, secondary sealing, and capacity division, a battery of about 10Ah was obtained.

[0119] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0120] Comparative Example 3

[0121] Positive electrode: Ni88(Li(Ni 0.88 Co 0.09 Mn 0.03 O 2)) The ternary material, conductive carbon black, carbon nanotubes and polyvinylidene fluoride are mixed in a mass ratio of 95:2:1:2, and the solvent NMP is added for homogenization to form a uniformly mixed positive electrode slurry. The viscosity of the slurry is controlled at 6000mPa·s. The slurry is coated on the positive electrode current collector aluminum foil by a coating machine, and the single-side surface density of the coating is controlled to be 18mg / cm 2 After the coated electrode is rolled, the thickness of the electrode is 120 μm. After die-cutting, it is placed in a 100°C oven for vacuum drying for 12 hours to obtain a positive electrode.

[0122] The negative electrode plate is the same as that in Example 3.

[0123] Solid-state battery dry cell: After the solid-state battery positive electrode sheet, negative electrode sheet, and solid electrolyte LATP coated diaphragm are stacked, welded, and top and side sealed, a solid-state battery soft-pack dry cell is obtained.

[0124] Electrolyte prepolymer: At room temperature, 3 wt% N,N-methylenebisacrylamide and 0.02 wt% benzoyl oxide initiator were added to 96.98 wt% organic electrolyte (1M LiPF 6 / EC+EMC+DMC), stirred for 30 minutes, and allowed to stand at room temperature for 12 hours to obtain an electrolyte prepolymer. The electrolyte prepolymer can be stored in a refrigerator with a shelf life of 7 days.

[0125] Solid-state battery: The dry cells of the solid-state battery are vacuum dried at 100°C for 18 hours, the electrolyte prepolymer is injected into the dry cells, and after being soaked at room temperature of 25°C for 36 hours, the cells are subjected to high-temperature treatment at 70°C and 600kgf pressure for 10 hours. After formation, aging, degassing, secondary sealing, and capacity separation, a solid-state battery is obtained.

[0126] The prepared solid-state battery was subjected to capacity and cycle electrical performance tests as well as heating, acupuncture and other safety performance tests. The test results are shown in Table 1.

[0127] Table 1

[0128]

[0129]

[0130] Through comparative examples 1-3, it can be seen that in comparative example 1, the positive electrode material has no in-situ solidification coating and no polymer solid electrolyte, and it fails the heating and acupuncture safety tests. In comparative example 2, the positive electrode material is coated with oxide in-situ, and there is a certain pass rate in the acupuncture safety test. In comparative example 3, the polymer solid electrolyte that is cured in-situ is used, and there is a certain pass rate in the heating and acupuncture safety tests. That is, simple oxide coating or simple polymer solid electrolyte has a certain improvement in safety.

[0131] Examples 1-6 combine in-situ cured coated inorganic oxides and polymer solid electrolytes to provide double insurance for battery safety. Compared with Comparative Examples 1-3, they can basically pass the heating and acupuncture safety tests. The oxide on the surface of the positive electrode material effectively blocks the contact between the active particles of the positive electrode material and improves the thermal stability of the material. At the same time, the oxide can absorb part of the heat generated by the positive electrode to alleviate the overheating of the positive electrode. The polymer obtained by in-situ polymerization solidifies the flowing electrolyte, which can effectively improve the contact between the oxide solid electrolyte and the material in the positive electrode sheet, improve the anti-short circuit performance of the battery cell and thus improve the safety performance.

[0132] Those skilled in the art should understand that the specific structures and processes shown in the above specific embodiments are only exemplary and not restrictive. Moreover, those skilled in the art can combine the various technical features shown above in various possible ways to form new technical solutions, or make other changes, which are all within the scope of the present invention.

Claims

1. A method for preparing an in-situ solidified organic-inorganic composite solid electrolyte, characterized in that: The method comprises the following steps: in the process of preparing the positive electrode sheet, in-situ curing is performed on the surface of the active positive electrode material to form an inorganic oxide layer; after being processed into a dry battery cell, an organic solid electrolyte is formed by in-situ curing.

2. The method for preparing the in-situ cured organic-inorganic composite solid electrolyte according to claim 1, characterized in that: The method comprises the following steps: mixing the positive electrode material, coating agent, conductive agent and binder, adding solvent N-methylpyrrolidone to form a slurry, coating the slurry on the positive electrode collector, baking, rolling and die-cutting, and placing the slurry in an oven for vacuum drying to form a positive electrode sheet of a solid-state battery.

3. The method for preparing the in-situ cured organic-inorganic composite solid electrolyte according to claim 2, characterized in that: The positive electrode material is at least one of lithium cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese aluminum oxide, and lithium iron phosphate; the coating agent is at least one of aluminum isopropoxide, titanium isopropoxide, titanium tetrachloride, tetra-n-butyl titanate, and tetraethoxysilane; the mass ratio of the positive electrode material, the coating agent, the conductive agent, and the binder is (80-97): (1-10): (1-5): (1-5); the temperature of the vacuum drying in the oven is 100-150° C., and the baking time is 12-48 hours.

4. An in-situ solidified organic-inorganic composite solid electrolyte, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 3.

5. A method for preparing an in-situ cured organic-inorganic composite solid-state battery, characterized in that: Comprising the steps as described in any one of claims 1 to 3, further The method comprises the following steps: after being processed into a dry battery core, an organic solid electrolyte is formed by in-situ solidification; after being chemically divided into different capacities, a solid-state battery with an organic-inorganic composite solid electrolyte is formed.

6. The method for preparing an in-situ cured organic-inorganic composite solid-state battery according to claim 5, characterized in that: The following steps are involved: The positive electrode material, coating agent, conductive agent and binder are mixed, and the solvent N-methylpyrrolidone is added to form a slurry, which is applied to the positive electrode collector, and after baking, rolling and die-cutting, it is placed in an oven for vacuum drying to form a positive electrode sheet of a solid-state battery; The positive electrode sheet, separator and negative electrode sheet of the solid-state battery are assembled into a dry battery cell by stacking, and after baking, the electrolyte prepolymer is injected. After room temperature infiltration and pressurized high-temperature polymerization, the cells are divided into volumes to obtain an organic-inorganic composite solid-state battery.

7. The method for preparing an in-situ cured organic-inorganic composite solid-state battery according to claim 6, characterized in that: The diaphragm is one of a ceramic coated diaphragm, a rubber coated diaphragm, and a solid electrolyte coated diaphragm; the negative electrode sheet is one of a graphite negative electrode sheet, a silicon carbon negative electrode sheet, a silicon oxide graphite negative electrode sheet, or a lithium metal negative electrode sheet; the immersion time is 12-48h; the pressure in the pressurized high temperature polymerization is 100-1000kgf, the temperature is 50-80°C, and the polymerization time is 3-24h.

8. The method for preparing an in-situ cured organic-inorganic composite solid-state battery according to claim 6 or 7, characterized in that: The electrolyte prepolymer is composed of three parts: organic electrolyte, polymer monomer and initiator; The mass percentages of the organic electrolyte, the polymer monomer and the initiator in the electrolyte prepolymer are: (80-99.7): (0.3-20): (0.005-1).

9. The method for preparing an in-situ cured organic-inorganic composite solid-state battery according to claim 8, characterized in that: The polymer monomer is selected from at least one of 1,3-dioxolane, methyl methacrylate, ethyl methacrylate, triethylene glycol methacrylate, di(trimethylolpropane) tetraacrylate, propylene glycol monomethyl ether acetate, vinylene carbonate, cyanopolyvinyl alcohol, ethylene acrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, polyethylene glycol diacrylate, polyethylene glycol methyl ether acrylate, 2-methacrylate-2-oxirane ethyl ester, polyethylene glycol diglycidyl ether, polyethylene glycol dimethyl ether, N,N-dimethylacrylamide, N,N-methylenebisacrylamide, etc.; The initiator comprises at least one of benzoyl peroxide, azobisisobutyronitrile, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, azobisisoheptylnitrile, dimethyl azobisisobutyrate, tri-n-butyl phosphine, triethyl phosphine, triphenyl phosphine, tributyltin oxide, stannous octoate, tetrabutyl zirconate, N-methylethylenediamine, dimethylformamide, aluminum trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, tin trifluoromethanesulfonate and lithium bis(fluorosulfonyl)imide, dialkyltin oxide and trialkyltin alkoxide.

10. An in-situ cured organic-inorganic composite solid-state battery, characterized in that: The invention is prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Method for modifying positive electrode of lithium ion battery by adding metal oxide / carbon composite material

    CN105390700A

  • Preparation method for improving high temperature cycling performance of lithium manganite by doping Al3<+> and F<->

    CN108258304A

  • Positive plate, preparation method thereof and application of positive plate in semi-solid battery

    CN113745454A

  • Battery pole piece, preparation method thereof and semi-solid lithium ion battery

    CN116093253A

  • Positive pole piece and electrochemical device thereof

    CN116314817A